Lactosylated liposomes for targeted delivery of doxorubicin to hepatocellular carcinoma - Zhou, Xiaoju (Dove Medical Press, 2012)
BACKGROUND: N-lactosyl-dioleoylphosphatidylethanolamine (Lac-DOPE) was synthesized and evaluated as a liver-specific targeting ligand via asialoglycoprotein receptors for liposomal delivery of doxorubicin. METHODS: Lactosylated liposomes encapsulating calcein (Lac-L-calcein) or doxorubicin (Lac-L-DOX) composed of egg phosphatidylcholine, cholesterol, monomethoxy polyethylene glycol 2000-distearoyl phosphatidylethanolamine, and Lac-DOPE at 50:35:5:10 (mol/mol) were prepared by polycarbonate membrane extrusion and evaluated in human hepatocellular carcinoma HepG2 cells. Cellular uptake of Lac-L-calcein was monitored by confocal microscopy and by flow cytometry. The cytotoxicity of Lac-L-DOX was evaluated by MTT assay. The pharmacokinetic properties of Lac-L-DOX were studied in normal mice, and its biodistribution and antitumor activity were studied in nude mice with HepG2 xenografts. RESULTS: The size of Lac-L-DOX was less than 100 nm and the liposomes demonstrated excellent colloidal stability. In vitro uptake of Lac-L-calcein by HepG2 cells was four times greater than that of non-targeted L-calcein. In the presence of 20 mM lactose, the uptake of Lac-L-calcein was inhibited, suggesting that asialoglycoprotein receptors mediated the observed cellular uptake. Lac-L-DOX exhibited enhanced in vivo cytotoxicity compared with the nontargeted liposomal doxorubicin (L-DOX), and its pharmacokinetic parameters indicate that Lac-L-DOX has a long blood circulation time (t(1/2) 8.73 hours). Tissue distribution and therapeutic efficacy studies in nude mice bearing HepG2 xenografts show that Lac-L-DOX had significantly stronger tumor inhibitory activity compared with L-DOX and free doxorubicin, along with a higher accumulation of drug within the tumor site and greater cellular uptake by tumor cells. CONCLUSION: These data suggest that lactosylated liposomes are promising drug delivery vehicles for hepatocellular carcinoma.